Uma cidade sempre nova produção do espaço e desenvolvimento urbano em Santa Rosa/RS (décadas de 1930 a 1960) - Schmitz, Maira Eveline (2023)
The research object of this thesis is the city of Santa Rosa, located in the northwest region of Rio Grande do Sul. The possibility of facing Santa Rosa as a new town was presented as a central defense, a term that refers to a temporal condition, but also to a specific urban identity. In this direction, the research analyzes the historical, material and symbolic elements, which allowed to delineate Santa Rosa as belonging to this which was a specific movement of creation of cities, occurred in Brazil of the 20th century. The research theme is delimited by a specific historical-cultural context, marked by the installation of transport and communication networks, by agricultural production, by the beginnings of the mechanization of agriculture and by industrial development, which characterized the environment as a mixture of urban and rural. The period of analysis was demarcated between the 1930s and 1960s, as it encompasses both the urban formation of the city and the socioeconomic transformations analyzed. The sources analyzed were, primarily, newspaper articles, photographs and plans and maps, adopting appropriate methodologies for each type of document. Historiographically, the research is inserted in the field of Urban History and its multiple possibilities, adopting the notion of space – and its social (re)production in time – as a tool for understanding urban practice. Focusing on the urban development process of the city in question, this work, as an exercise in historical and historiographical reflection, helped to deepen the understanding of the history of cities and urbanism, beyond the traditional explanatory models.